APAKAH GOOD CORPORATE GOVERNANCE MEMPENGARUHI PENGUNGKAPAN SUSTAINABILITY REPORT? - Pramesti, Anisa Sekar; Hardiningsih, Pancawati (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
The study aims to test good corporate governance factors against the disclosure of sustainability reports at IDX banking companies for the period 2016 – 2020. Purposive Sampling is a sampling method used in this study, the amount of data processed is 35 companies. Using multiple linear regression analysis tools. This research show that good corporate governance and profitabilitas has a positive effect an plant persistence. Meanwhile, leverage have a significant negative impact on the disclosure of sustainability reports.